2019
DOI: 10.3390/ma12020212
|View full text |Cite
|
Sign up to set email alerts
|

A Novel PAN-GO-SiO2 Hybrid Membrane for Separating Oil and Water from Emulsified Mixture

Abstract: In this article, we report the development of a polyacrylonitrile-graphene oxide-silicon dioxide (PAN-GO-SiO2) hybrid membrane for separation of oil and water from their emulsified mixture. The membrane was successfully fabricated using a one-step electrospinning process. GO and SiO2 nanofillers were added in PAN in different concentrations to determine the optimized composition for the PAN-GO-SiO2 hybrid membrane. A scanning electron microscopy (SEM) examination showed that the nanofillers were uniformly embe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 40 publications
3
31
0
Order By: Relevance
“…Research results indicated that increasing the hydrophilicity of the membrane prevented membrane fouling and improved membrane permeability [4,16,22].…”
Section: Resultsmentioning
confidence: 99%
“…Research results indicated that increasing the hydrophilicity of the membrane prevented membrane fouling and improved membrane permeability [4,16,22].…”
Section: Resultsmentioning
confidence: 99%
“…The composite nanofibers with the GO amount over 10 wt % appeared to be rougher than those with the lower GO amount, but did not show any detectable defects (e.g., beads and nodes). It is noted that the integration of bare GO into PAN typically reaches around 5 wt % [ 19 , 31 , 32 , 33 , 34 ], whereas only a few studies describe the loading of GO up to 15 wt % into PAN nanofibers that required some chemical modifications and the use of additives [ 9 , 24 ]. Unlike polymer matrix modification, stabilizing the guest GO with CTAC via electrostatic interactions greatly increased its miscibility with PAN polymers in a DMF solution to prevent the clogging and/or phase separation during 6 h of electrospinning.…”
Section: Resultsmentioning
confidence: 99%
“…However, the use of fillers also requires the extensive optimization of the electrospinning conditions via trial and error to avoid the destruction of their original structures due to their immiscibility [ 1 , 2 ]. Among many filler materials [ 8 , 15 , 16 , 17 , 18 , 19 , 20 ], graphene oxide (GO) is of particular interest because it is inexpensive and possesses various physical properties, as well as easy surface functionalization. The integration of GO into polymeric materials has several potential advantages, including promoting an increase in the mechanical strength, permeability, selectivity, and antifouling properties [ 10 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we utilize a bottom-up method to grow well-defined, discretely distributed copper nanocubes on aligned polyacrylonitrile (PAN) nanofibers and microfibers based on electroless deposition from aqueous solutions. The interesting mix of hydrophilicity, chemical stability, and strong mechanical performance of electrospun PAN fibers has enabled their widespread adoption and adaptability as functional scaffolds for diverse application designs [ 17 , 18 ]. Furthermore, metallic nanocubes classically possess a high surface area harnessed for catalysis, and through anchoring on electrospun fibers, a surface area synergy is achieved that enhances functional efficacy [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%